IMPROVING INFORMATION SUPPORT OF CRISIS MANAGEMENT BY ENTERPRISES ON THE BASIS OF USING COMMUNICATION TOOLS OF THE TECHNOLOGICAL PLATFORM - M. N. Belousova; V. A. Belousov (Вестник университета)
Information support of crisis management requires the creation of a communication infrastructure, based on the program-target method, within which technological standards and profiles are formed – technological platforms. The information support of the crisis management of enterprises, based on the use of communication tools of the technological platform, as an interface of the innovative infrastructure, allowing increase the efficiency of the information component of the enterprise management system, has been improved in the paper. Based on the technological platform, new research and production cooperations, innovation clusters will be formed, which will allow overcome the crisis state of enterprises.